Development of an Amperometric Glucose Biosensor Based on the Immobilization of Glucose Oxidase on the Se-MCM-41 Mesoporous Composite - Sabriye Yusan; Mokhlesur M. Rahman; Nasir Mohamad; Tengku M. Arrif; Ahmad Zubaidi A. Latif; Mohd Aznan M. A.; Wan Sani B. Wan Nik (Journal of Analytical Methods in Chemistry)
A new bioenzymatic glucose biosensor for selective and sensitive detection of glucose was developed by the immobilization of glucose oxidase (GOD) onto selenium nanoparticle-mesoporous silica composite (MCM-41) matrix and then prepared as a carbon paste electrode (CPE). Cyclic voltammetry was employed to probe the catalytic behavior of the biosensor. A linear calibration plot is obtained over a wide concentration range of glucose from 1 × 10−5 to 2 × 10−3 M. Under optimal conditions, the biosensor exhibits high sensitivity (0.34 µA·mM−1), low detection limit (1 × 10−4 M), high affinity to glucose (Km = 0.02 mM), and also good reproducibility (R.S.D. 2.8%, n=10) and a stability of about ten days when stored dry at +4°C. Besides, the effects of pH value, scan rate, mediator effects on the glucose current, and electroactive interference of the biosensor were also discussed. As a result, the biosensor exhibited an excellent electrocatalytic response to glucose as well as unique stability and reproducibility.